The status of mycology in Africa: A document to promote awareness - M. Gryzenhout; J.M. Jefwa; N.S. Yorou (IMA Fungus)
The African Mycological Association (AMA) promotes mycology amongst members in Africa and globally. The AMA has about 200 members, mostly from African states but also with strong representation from Europe and USA, amongst others. Recent efforts by members of the AMA focused on reviving and developing mycological research and networking in Africa. A great deal must, however, still be done to promote the AMA under African mycologists, and those elsewhere with interests in Africa. African mycologists also experience challenges typical of the developing world and a great deal of fungi still needs to be discovered. This can also be seen as representing great opportunities for research and collaboration. Several issues pertinent to mycology in Africa were discussed during Special Interest Group sessions of the 9th International Mycological Congress in 2010, and through several opinion pieces contributed by AMA members in the AMA newsletter, MycoAfrica. This contribution serves as a document to summarise these in a form that can be presented to fellow mycologists, biologists and other scientists, relevant government departments, funding bodies and Non-Governmental Organizations and that pins down the importance of mycology, the status thereof in Africa and the need to promote it more.